Barrierless Free Charge Generation in the High‐Performance PM6:Y6 Bulk Heterojunction Non‐Fullerene Solar Cell. Issue 9 (24th January 2020) - Perdigón‐Toro, Lorena; Zhang, Huotian; Markina, Anastasia; Yuan, Jun; Hosseini, Seyed Mehrdad; Wolff, Christian M.; Zuo, Guangzheng; Stolterfoht, Martin; Zou, Yingping; Gao, Feng; Andrienko, Denis; Shoaee, Safa; et al.
Abstract: Organic solar cells are currently experiencing a second golden age thanks to the development of novel non‐fullerene acceptors (NFAs). Surprisingly, some of these blends exhibit high efficiencies despite a low energy offset at the heterojunction. Herein, free charge generation in the high‐performance blend of the donor polymer PM6 with the NFA Y6 is thoroughly investigated as a function of internal field, temperature and excitation energy. Results show that photocurrent generation is essentially barrierless with near‐unity efficiency, regardless of excitation energy. Efficient charge separation is maintained over a wide temperature range, down to 100 K, despite the small driving force for charge generation. Studies on a blend with a low concentration of the NFA, measurements of the energetic disorder, and theoretical modeling suggest that CT state dissociation is assisted by the electrostatic interfacial field which for Y6 is large enough to compensate the Coulomb dissociation barrier. Abstract : The efficiency of photocurrent generation is studied in the high‐efficiency nonfullerene PM6:Y6 blend, using a combination of field‐ and temperature‐dependent optoelectronic measurements. These experiments reveal barrierless free charge generation, despite a small driving force. Theoretical modeling suggests the existence of a large electrostatic interfacial field, which pushes charges away from the donor–acceptor interface.